Produção e qualidade de sementes de genótipos de grão-de-bico em diferentes épocas de plantio no Norte de Minas Gerais - Humberto Alencar Paraiso (2019)
The chickpea is a legume of high nutritional value that participates in the feeding of thousands of people around the world. Originating in regions of Syria and Turkey is considered a plant with a dry and cold climate, but adapts very well in regions of tropical climate, as is the case of Brazil, when cultivated in winter. In northern Minas Gerais, winter is dry and temperatures are mild, conditions conducive to the development of chickpea culture and the production of quality seeds. The objective of the study was to evaluate the production and seed quality of chickpea genotypes under irrigated system in the municipality of Montes Claros, North of Minas Gerais, due to three planting seasons. For this, the experiment was divided into two parts. The first part of the experiment was conducted in the field, in an experimental area of the Institute of Agrarian Sciences of the Federal University of Minas Gerais (ICA / UFMG), from April to October 2017. A randomized complete block design (DBC) with four replicates, in a 4x3 factorial scheme, four genotypes of chickpea (Cicero, BRS Aleppo, CNPH01-17 and CNPH02-17) and three planting seasons (April 27, 31, and July 2). The plots were formed by four lines of 3 meters in length, spaced 0.50 m apart, with a planting density of 10 seeds per linear meter. The evaluated characteristics were: seedling emergence characterization, number of days for beginning and full flowering, and beginning and full pod formation, plant height, total biomass, grain yield, harvest index and number of pods per plant. The second part of the experiment was carried out in the Laboratory of Seed Analysis (LAS / ICA) from November 2017 to January 2018. The design was a completely randomized design (DIC), in a 4 x 3 factorial scheme. The seeds obtained from the four genotypes of chickpea (Cicero, BRS Aleppo, CNPH01-17 and CNPH02-17) and the three planting seasons (April/27, May/31 and July/02) of the first part of the experiment. In each of the epochs, a sample composed of seeds for each genotype was formed and, later, they were sent to the laboratory for the analysis. Seed quality, dry matter, biometry and weight of 1000 seeds were determined for seed physical quality. The physiological quality of the seeds was evaluated by the germination test, first germination test count, germination speed index (IVG) and total seedling length. The data were submitted to analysis of variance and the means compared to a 5% probability by the Tukey test in the statistical program R. The studied genotypes presented good productive performance with yields higher than 2000 kg ha-1 and in some cases as of the genotypes Cicero and CNPH01-17 exceeding 3000 kg ha-1. The genotypes BRS Aleppo, CNPH01-17 and CNPH02-17 presented excellent quality seeds with germination percentage above 80% in all planting seasons. However, the quality of the seeds of the Cicero genotype was compromised when the planting was carried out in the month of July. The North of Minas Gerais has high potential in the quality seed production of chickpea when cultivated in the winter under the irrigated system.